Psychological The Educating Multicultural Personality in Tadarus al-Qur'an Activities in WhatsApp Groups - Saliyo, Saliyo; Saefuddin, Saefuddin; Sophian, Muhamad (Kawanua International Journal of Multicultural Studies, 2025)
The development of information and communication technology has produced both challenges and opportunities within multicultural education. While digital interaction may trigger social tension when users lack adaptability, it also offers potential to promote spiritual practice and religious tolerance. This study examines the role of WhatsApp groups as a medium for fostering tolerant behavior through collective Qur’an reading (tadarus). Using a qualitative approach, data were collected from 11 participants selected through purposive sampling and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that participation in Qur’an reading groups enhances spiritual motivation, emotional calmness, positive attitudes, and habit formation. Participants also reported strengthened faith, acceptance of life circumstances, and improved subjective well-being. The study concludes that WhatsApp-based religious activities positively shape social and spiritual personality while supporting tolerant behavior in multicultural contexts.